Clinical audiology - Stach, Brad A. (Singular Publ., 1998)
Clinical Audiology: An Introduction is a stimulating, introductory - level textbook that provides a "big-picture" overview of the field of audiology. It introduces the student to the broad scope of the field, with the aim that they will be better prepared to understand the relevance of what they learn later on. This text provides general familiarization with the many different evaluative and rehabilitative technologies and demonstrates how these technologies are integrated into answering the many challenging clinical questions facing an audiologist. Focusing on the clinical nature of audiology, this essential book provides students with questions, challenges, and technologies available to address issues of hearing impairment and rehabilitation